Formation mechanism of microstructure in two-phase zone continuous casting Cu–Sn alloy. (11th June 2018) - Luo, Jihui; Liu, Xuefeng; Yang, Kun
ABSTRACT: The microstructure of two-phase zone continuous casting Cu–4.7Sn (in wt. % as default) alloy was investigated by optical microscope and electron backscattering diffraction. Numerical simulation software ProCAST was used to simulate the microstructure evolution of TZCC Cu–4.7Sn alloy. The process and formation mechanism of microstructure in TZCC Cu–4.7Sn alloy were discussed. The results show that the nucleation of small grains occurs in front of the solid–liquid interface during the TZCC Cu–4.7Sn alloy. The angular difference between the [001] direction of columnar grains and the solidification direction is small, which has faster growth speed. The angular difference between the [001] direction of the small grains and the solidification direction is large, which has slower growth speed. While the small grains are in contact with the columnar grains, the growth speed of the columnar grains in the preferred orientation [001] is faster, and the small grains are "annihated" to form grain-covered grains and small grains at columnar grain boundaries.